Role of Tiotropium as Step Up Therapy for Asthma - Muhammad Usman Ullah, M Babar Khan. Jahanzeb Liaqat, Raheel Iftikhar, Sultan Mehmood Kamran, Aamir Khalil, (Journal of Rawalpindi Medical College, 2013)
Background: To determine the role of Tiotropium as step up therapy for patients with uncontrolled asthma. Methods: In this case control study 130 patients, with diagnosis of bronchial asthma for at least 01 year and presently on step 4 treatment and still symptomatic, were included . Sixty five patients were randomly assigned to receive Tiotropium bromide dried inhaler added to their conventional step 4 treatment, whereas 65 patients were given placebo. Patients were asked about symptomatic improvement, using mini AQLQ. Peak Expiratory Flow Rate (PEFR) was checked eight weeks after wards to document response to therapy. Results: Mean age and duration of diagnosis of asthma was 38 years and 5.1 years, respectively in cases. Mean PEFR at admission among cases was 210 l/min (± 58.35) while it was 203 l/min (± 57.32) among controls. Frequency of nocturnal awakening were 2.98 days/ week among cases and 2.88 days/ week among controls. At week 8, frequency of nocturnal symptoms was found to be 1.6 days/week among patients on Tiotropium while it was 2.13 days /week among controls. Mean PEF was 387 l/min among Tiotropium group as compared to 305 l/min. There was statistically significant improvement in symptoms and PEFR of patients on Tiotropium as compared to controls. (p value 0.004). The differences remained statistically significant after adjusting for age and gender. Conclusion: Tiotropium daily as maintenance treatment through dried inhaler in addition to at least high-dose inhaled corticosteroids combined with long acting B2 agonists offers significant potential to improve airway patency in patients with severe persistent asthma who are still symptomatic and obstructed on maximal therapy.